The development of a digital-based learning evaluation tool using wordwall media for persuasive text material in elementary school - Habib Maulana; Muhtarom; Ngatmini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Evaluation is essential to the learning process to assess students' understanding. One of the innovations in learning evaluation is using digital media, such as the Wordwall platform. This study aims to describe the development process of the learning evaluation tool, analyze its effectiveness, and assess its practicality. The research used a development research approach using the ADDIE model, which consisted of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research subjects included fifth-grade students at SDN Pamulian 01 and experts (subject matter experts, media experts, and language experts). The validation results show that the content validity percentage is 93%, while the media validity percentage is 93.75%, meeting the